2005
DOI: 10.1111/j.1875-595x.2005.tb00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Sealing effectiveness of materials used in furcation perforation in vitro

Abstract: MTA alone or Vitremer in combination with a collagen sponge can be used effectively in the treatment of perforations in a furcation area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
1
17
1
2
Order By: Relevance
“…39,40 Glass-ionomer cement was found to be superior compared with composite resin, amalgam, temporary dental restorative material (Cavit W) and tricalcium phosphate when used in furcation perforation repair in previous studies. 2,6,8,19,41 However, when the MTA cement was introduced, it showed increased resistance to leakage in furcal perforations compared with glass-ionomer cement. 9,23 A similar trend was seen in the present study, but the difference between the MTAs and the glass ionomer cements was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39,40 Glass-ionomer cement was found to be superior compared with composite resin, amalgam, temporary dental restorative material (Cavit W) and tricalcium phosphate when used in furcation perforation repair in previous studies. 2,6,8,19,41 However, when the MTA cement was introduced, it showed increased resistance to leakage in furcal perforations compared with glass-ionomer cement. 9,23 A similar trend was seen in the present study, but the difference between the MTAs and the glass ionomer cements was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Glass ionomer cements are used in surgical endodontics 10,17 and they have been advocated for use as a perforation repair material as well. One advantage is its adhesiveness to dentine, and several studies demonstrate its good sealing ability both in vitro 2,6,8,[18][19][20] and in vivo. 21,22 However, other studies have shown that resin modified glass ionomer cement showed more microleakage and less sealing ability compared to MTA cement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral trioxide aggregate (MTA) (Dentsply, Tulsa, OK), which was first introduced as a root-end filling material by Torabinejad et al (4) in 1993, has been widely used in endodontic therapy (5). Compared with other root-end filling materials, MTA displays significant advantages in terms of its biocompatibility and osteoconduction ability (1,(6)(7)(8)(9). Now MTA is considered as gold standard repair material for several clinical applications including the repair of perforation, root-end filling, the repair of root resorption, apexification, and pulp capping.…”
mentioning
confidence: 99%
“…In recent era, Mineral trioxide aggregate (MTA) has taken attention in pulpotomy of mature permanent tooth because of its excellent sealing ability 4 , biocompatibility 5 , dentin bridge formation 6,7 properties. Few studies were performed regarding the clinical and radiographic evaluation of MTA as a pulpotomy agent in mature permanent teeth with irreversible pulpitis, stating that the probability of survival without any other intervention after MTA pulpotomy in mature permanent teeth is around 82% 8 and 100%.…”
Section: Introductionmentioning
confidence: 99%